2006
DOI: 10.1016/j.ejvs.2006.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Sympathectomy for Raynaud's Phenomenon—A Long Term Follow-up Study

Abstract: The majority of patients with Raynaud's phenomenon have an excellent immediate effect from thoracoscopic sympathectomy and one third achieve a long lasting effect. Side effects are frequent. We now only use thoracoscopic sympathectomy in severe cases of Raynaud's phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…2 A recent longitudinal follow-up study of patients undergoing thoracoscopic sympathectomy found that one third of patients had a long-lasting benefit by 40 months of follow-up. 3 Recurrence of symptoms after ETS treatment for Raynaud's phenomenon is likely to be multi-factorial and may not reflect failure of the procedure. Maga et al examined the microcirculatory status in 25 patients who received ETS for Raynaud's disease during the 5 years post procedure.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent longitudinal follow-up study of patients undergoing thoracoscopic sympathectomy found that one third of patients had a long-lasting benefit by 40 months of follow-up. 3 Recurrence of symptoms after ETS treatment for Raynaud's phenomenon is likely to be multi-factorial and may not reflect failure of the procedure. Maga et al examined the microcirculatory status in 25 patients who received ETS for Raynaud's disease during the 5 years post procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This case showed that a thorough physical and radiological examination of the thorax carried out before endoscopic thoracic sympathectomy 3 , which is an advanced therapeutic approach in serious RP patients who experience frequent bouts and have trophic changes due to insufficient treatment can prevent complications during surgery by allowing identification of deformities such as PE. Further, identification of this co-existence enabled concurrent utilization of thoracoscopic surgical treatments for RP and PE.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients with disorders of perfusion in the upper limbs experienced recurrence of complaints, after more than 5 years there was reduction of frequency and severity of attacks reported in 89.3% of patients 17 . Thune reports short term success of thoracoscopic sympathectomy of 83% in a group of 34 patients with Raynaud's phenomenon 18 . Long term effect however was reported only in one third of the patients.…”
Section: Discussionmentioning
confidence: 99%